Implementasi Media Kapla dalam Menumbuhkan Pemahaman dan Imajinasi Geometris Anak Usia Dini - Siti Masniah Nurkhayatin; Helina Himmatul Ulya Lina; Latifatus Sa'adah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to describe how the use of Kapla media fosters geometric understanding and imagination among Group A children at RA Muslimat XVII Keser Blora. The study employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The results indicate that Kapla media helps children recognize geometric shapes, differentiate sizes, and gradually construct patterns. Children who initially experienced difficulties became able to classify shapes, build simple patterns, and reconstruct collapsed structures with greater patience. Children’s imagination also developed through the courage to create new forms, modify constructions, and creatively express ideas. The learning atmosphere became more dynamic as children showed increased enthusiasm, active interaction, and collaboration within groups. These findings suggest that Kapla media is effective in enhancing early childhood geometric understanding, creativity, and imagination, and they provide practical implications for teachers to integrate constructive play as an enjoyable and meaningful learning strategy.